Znaczenie opieki nad wnukami w jakości życia osób w podeszłym wieku - Czepczarz, Jarosław; Czepczarz, Agata (Wydawnictwo Naukowe EDUsfera. Ewa Jurczyk-Romanowska, 2021)
A family is man’s first social group in which they function. The majority ofolder people feel a strong need to possess good family ties. Elders can be responsible for various household chores, if their health permits it. Grandparents relieve the professionally active younger generation of duties, giving them in return a sense of self in the genera lfunctioning of the family. Often times, for a variety of reasons, parents decide to leave their offspring in the care of their grandparents, without regard to the health impacts it has onthe older people
Keywords: caring for grandchildren; grandmothers; grandfathers; family